PEMEROLEHAN BAHASA MELAYU DIALEK SAMBAS PADA ANAK USIA 2â”€3 TAHUN ASPEK FONOLOGI (KAJIAN PSIKOLINGUISTIK - Murtaja, Indah; Patriantoro, Patriantoro; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study describes the phoneme acquisition of children aged 2"“3 years in Sambas Malay Dialect, as well as environmental influences that influence language acquisition. The method used is descriptive method with a qualitative research form. Sources of research data are children with an age range of 2âˆ’3 years. The data in this study are words and phrases. Data collection techniques are observation, interviews, tapping, listening to engagement, recording, and taking notes. Data collection tools are gadgets and notebooks. Testing the validity of the data is done with the persistence of observers and adequacy of references. The data obtained by the first subject amounted to 26, the second subject 49, and the third subject 58 utterances. The results of the first subject analysis obtained four consonant phonemes and three vowel phonemes. The phonemes produced by the second subject are eleven consonant phonemes and four vowel phonemes. The phonemes produced by the third subject are ten consonant phonemes and three vowel phonemes. Factors that influence language acquisition are biology, environment, intelligence, and motivation. Implementation of learning is in the form of an e-module text of the report on the results of observations in class X odd semester.